Будинок полкової канцелярії у 50-х роках ХІХ ст. - Доценко, А. (Сiверянський лiтопис, 2016)
Дана стаття є продовженням попередніх, надрукованих у журналах «Сіверянський
літопис» № 3 і № 6 за 2015 рік.
У публікації на архівних матеріалах Державного архіву Чернігівської області
висвітлюється історія наступного ремонту будинку полкової канцелярії у м. Чернігові
— 1855–1859 рр. І хоча тільки-но закінчився попередній капітальний ремонт, що тривав більше 5 років, у тому ж таки 1855 році почався наступний, не менш потужний і об’ємний, аніж попередній, і який також тривав 5 років. Данная статья является продолжением статей, опубликованных в журналах
«Сіверянський літопис» № 3 и № 6 за 2015 г.
В статье на архивных материалах Государственного архива Черниговской области
освещается история следующего ремонта дома полковой канцелярии в г. Чернигове —
ремонта 1855–1859 гг. И хотя только-только закончился предыдущий капитальный ремонт, который продолжался более 5 лет, снова, в том же 1855 г., начался следующий ремонт, не менее объемный, нежели предыдущий, и который тоже длился 5 лет. This article is a logical continuation of the articles published in the journal «Sіveryansky
lіtopis» №3 and №6 in 2015.
In the article based on the archival materials of the State Archives of Chernihiv region
tells the story of the next home renovations of Regimental Chancellery in Chernihiv-repairs
in 1855-59. And although just completed the previous major overhaul, which continued more
than five years, in the same 1855 began the next, not less powerful and voluminous than the
previous one, and wnich continued is also five years.
This time the repair works concerning the strengthening of truss constructions in the attic,
that due to the weight of archival papers caved, destroyed cornice from outside, that threatened
the fall of the home`s roof; repair of external cornice, stucco walls, which was damaged by
humidity, and also making and placing shelves for archival documents.